Effect of preoperative urethral dilatation on preventing urethral stricture after holmium laser enucleation of the prostate: A randomized, controlled study - Park, Jong Kwan; Kim, Ji Yong; You, Jae Hyung; Choi, Bo Ram; Kam, Sung Chul; Kim, Myung Ki; Jeong, Young Beom; Shin, Yu Seob (Canadian Urological Association Journal, 2019)
Introduction: We aimed to evaluate the effect of preoperative urethral dilatation during holmium laser enucleation of the prostate (HoLEP) on the prevention of urethral stricture. Methods: A total of 72 patients without urethral stricture underwent HoLEP for benign prostatic hyperplasia (BPH). Recruited patients were randomly divided into two groups (groups A and B). Patients in group A (36 patients, experimental group) received preoperative urethral dilatation and patients in group B (36 patients, control group) did not. Each patient was evaluated at four weeks, 12 weeks, and 24 weeks after surgery. The effectiveness of preoperative urethral dilatation was evaluated based on the International Prostate Symptom Score (IPSS), peak urine flow rate (Qmax), voided volume, and post-void residual (PVR) volume. To diagnose urethral stricture, Qmax <10 mL/s, as assessed using uroflowmetry and findings of visualization through retrograde urethrography and urethroscopy, were used. Results: Among 72 initial participants, 33 patients in group A and 31 patients in group B completed the experiment. Preoperative characteristics were well-balanced between groups. At each postoperative visit, there was no significant difference in voiding symptoms between groups. Two patients (6.06%) in group A and five patients (15.15%) in group B showed a Qmax <10 mL/s on uroflowmetry (p=0.013). On urethroscopy, no patient in group A (0%) and two patients in group B (6.45%) (p=0.021) showed urethral stricture after HoLEP. Conclusions: Preoperative urethral dilatation during HoLEP decreased the incidence of urethral stricture. This procedure could be useful to reduce the risk of urethral stricture after transurethral prostate surgery. One limitation of the current study is the single-center design. Also, we sought to determine the efficacy of preoperative urethral dilatation for the prevention of urethral stricture after transurethral prostate surgery within a short time period, which could be another limitation of the study. Despite these limitations, to the best of our knowledge, the present study is the first reported prospective, randomized trial analyzing the safety and efficacy of preoperative urethral dilatation for the prevention of urethral stricture after transurethral prostate surgery.